2014
DOI: 10.1039/c4ta01444h
|View full text |Cite
|
Sign up to set email alerts
|

AgBr quantum dots decorated mesoporous Bi2WO6architectures with enhanced photocatalytic activities for methylene blue

Abstract: AgBr quantum dots (QDs) were decorated on the surface of Bi2WO6 to form a novel AgBr/Bi2WO6 heterojunction. The enhancement of catalytic efficiency of AgBr/Bi2WO6 heterojunctions relative to pure Bi2WO6 could be associated to differences in their lifetime as holes and electrons, and to valence and conduction band positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(104 citation statements)
references
References 80 publications
(69 reference statements)
6
98
0
Order By: Relevance
“…Two peaks centered at 35.7 eV and 37.8 eV (Figure 3c) are respectively assigned to 4f7/2 and 4f5/2 from W 6+ element which is in accord with the reported values [15]. The sharp and a slightly non-symmetric O1s peak located at the binding energy of 529.9 eV (Figure 3d) may be from the main contribution of crystal lattice oxygen and adsorbed oxygen in the oxide [16]. …”
Section: Structure and Morphologysupporting
confidence: 79%
“…Two peaks centered at 35.7 eV and 37.8 eV (Figure 3c) are respectively assigned to 4f7/2 and 4f5/2 from W 6+ element which is in accord with the reported values [15]. The sharp and a slightly non-symmetric O1s peak located at the binding energy of 529.9 eV (Figure 3d) may be from the main contribution of crystal lattice oxygen and adsorbed oxygen in the oxide [16]. …”
Section: Structure and Morphologysupporting
confidence: 79%
“…The electron of the excited state is directly injected into the conduction band (CB) of the semiconductor. In general, degradation proceeds it could be concluded that the suppression of electron-hole recombination and generation of more Å OH radicals in samples play an important role in the enhanced rate of photo-mineralization [19]. In photocatalytic oxidation experiments, organic contaminants are removed using the semiconductor in the presence of light.…”
Section: Photoelectrocatalytic Degradation Of Salicylic Acidmentioning
confidence: 99%
“…Semiconductor photocatalysis has been recently proposed as a potential pathway to address this, through the photocatalytic degradation of environmentally harmful pollutants [3][4][5]. Among the photocatalysts proposed, TiO 2 is the most advantageous due to its stability, nontoxicity, and low cost [6,7].…”
Section: Introductionmentioning
confidence: 99%